Influência das fases de anestro e diestro na competência meiótica oocitária de cadelas - Pereira, Leda Maria Costa [UNESP]; Bersano, Paulo Ricardo de Oliveira [UNESP]; Lima, Alfredo Feio da Maia [UNESP]; Pantoja, José Carlos de Figueiredo [UNESP]; Lopes, Maria Denise [UNESP] (Universidade de São Paulo. Agência de Bibliotecas e Coleções Digitais, 2015)
The bitch has reproductive peculiarities that differentiate it from other species. Several experiments have been conducted to establish efficient protocols for maturation; however, the results appear to be unsatisfactory. In this respect, the reproductive female donor should be considered, since it can be a factor of variability of findings in this species. The objective of this study was to evaluate the relationship between the estrous cycle phases - phase diestrus and anestrus on canine oocyte in vitro maturation (IVM). The ovaries were transported in sodium chloride 0.9% solution, and were cut into phosphate-buffered saline (PBS) and the cumulus-oocyte complexes (COCs) selected in tissue culture medium (TCM), supplemented with 199 HEPES. A total of 469 grade 1 oocytes were collected from bitches in anestrus and diestrus. These selected oocytes were transferred to the maturation medium for a period of 72 hours, then subjected to hyaluronidase solution and stained with Hoechst 33342 to assess nuclear configuration. The comparison of anestrus and diestrus phase showed no differences (p > 0.05) between the nuclear maturation stages. Thus, the phase of the estrous cycle did not influence the in vitro maturation of canine oocytes, increasing the rates of M-II in this species.
Influence of anestrus and diestrus stages of oocyte on meiotic competence in bitches
Keywords: Bitch; Estrous cycle; Maturation; Reproductive stage